Estudos de citotoxicidade e genotoxicidade no gênero Baccharis L. - Almeida, Taiane Nogueira (2021)
Species of the Baccharis genus have many compounds with biological activitiy. Because of the wide use in folk medicine, it is essential that studies in relation to the potential toxic compounds are extended.The information collected for this integrative review seek to provide an overview of the general aspect of genotoxic and cytotoxic studies of essential oils, extracts, fractions and pure compounds for this genus, in order to guide future research. Data searches were performed using Boolean operators (AND) to perform the combination of termsin the PubMed, Web Of Science, Scopus, LILACS e SciELOdatabases. The investigation resulted in a total of 106 articles, of which 41 are from 2015 until June 2021. Of the 21 studied species of the genus Baccharis, Baccharis dracunculifolia stands out as the most frequent, followed by Baccharis trimera. Of the natural products, the species extract was the most researched.Among the models studied, normal cells of human and/or mammalian origin and cancer cells were the most used for cytotoxicity effects, while for genotoxicity studies, the types of models extended from normal cells and cancer cells to bacteria and seeds of Allium cepa. The researches focus on investigating the cytotoxic and genotoxic responses, to evaluate mainly the following biological activities: gastroprotective, immunomodulatory, antiprotozoal, anticancer, anti-adipogenic, antioxidant, antimicrobial effects, among others. Selective cytotoxicity responses stand out, prioritizing not drastically affecting normal human cells, and compounds with antigenotoxicity/genoprotector properties. In addition to studies with a medicinal and pharmacological focus, there was the discussion of economic and environmental aspects. Studies confirm that species and their properties have the potential to treat important diseases in the present and future.